PP13 New signs to encourage the use of automated external defibrillators by the lay public. Issue 10 (28th September 2017) - Smith, Christopher M; Colquhoun, Michael C; Samuels, Marc; Hodson, Mark; O'Sullivan, Judy; Mitchell, Sarah
Abstract : Background: Public Access Defibrillation – the use of Automated External Defibrillators (AEDs) by lay bystanders before the arrival of Emergency Medical Services – is an important strategy in delivering prompt defibrillation to victims of out-of-hospital cardiac arrest and can greatly improve survival rates. Such public-access AEDs are used rarely: one barrier might be poor understanding and content of current signage to indicate their presence. The aim of this project was to develop a sign, with public consultation, that better indicated the function of an AED and an associated poster to encourage its use. Methods: Two public surveys were undertaken, in July and December 2015, to investigate perceptions of the current AED location sign recommended for use in the UK and to produce an improved location sign and associated information poster. Results: 1895 and 2115 respondents to the surveys. Fewer than half (47.9%, 895/1870) understood what the current location sign indicated. One of four design options for a location sign best explained the indication for (preferred by 56.0%, 1023/1828) and best encouraged the use of a public AED (51.8%, 946/1828). 83.5% (1766/2115) preferred an illustration of a stylised heart trace to the lightning bolt used at present. From five wording options, 'Defibrillator – Heart Restarter' was the most popular (29.4%, 622/2115). An associated poster was developed using design features from the new location sign, findings from the surveys and expert group input regarding its content. Conclusions: This is the first time that public consultation has been used to design a public AED location sign. Effective signage has the potential to help break down the barriers to more widespread use of AEDs in public places.